Trend of Hospital Admission and Outcome Study of Patients Admitted in a Neurology Unit at a Tertiary Care Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Neurological disorders is becoming a growing concern both for developed and developing countries. Magnitude of the problem is increasing day by day. Among all neurological disorders, stroke is the leading cause of morbidity and mortality globally.Objectives: The purpose of the study was to see the trend of admission of patients with neurological diseases and to study the outcome of patients at referral neurology hospital in Bangladesh.Methodology: This retrospective chart review was conducted in the blue unit of the Department of Neurology at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from 1st January to 31st December 2016 for a period of one (01) year. All the admitted patients with both sexes were selected as study population. The outcome was observed among the study population.Result: A total number of 1044 patients were admitted during the study period. Majority of the patients were in the age group of the 41 to 50 years which was 417(39.9%) cases. Both male and female were in highest number in the month of May which was 63 and 48 cases respectively. The total death of the study population was 146(14.0%) cases. The mean length of hospital stay was 8.4±2.31 days.Conclusion: Middle aged male is the main bulk of the neurological patients, admitted in a referral neurology hospital in Bangladesh. Highest admission and mortality was observed in stroke patients.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 69-74